2021
DOI: 10.1007/s00420-020-01645-z
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and respiratory symptoms and lung function among hairdressers in Iran: a cross-sectional study

Abstract: Objective Exposures at hairdressers’ work have been reported to lead to an increased risk of several health outcomes. The present study aimed to investigate the relations between occupational exposures and respiratory symptoms and lung function among hairdressers in Iran. Methods We conducted a cross-sectional study to compare potential respiratory effects among 140 women working as hairdressers to such effects among 140 women working as office workers (ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Bearing those differences in mind and accounting for influences from special subgroups studied (e.g. apprentices), demographics and tenure time were mostly in line with the expectations for hairdressers from the full spectrum of the working population [ 1 , 2 , 4 , 5 , 21 , 22 ]. While current smokers were found to a lesser extent than often described [ 3 , 21 , 22 , 32 ], the prevalence was comparable to current data from the German female population (18.6%) [ 33 ].…”
Section: Discussionsupporting
confidence: 58%
“…Bearing those differences in mind and accounting for influences from special subgroups studied (e.g. apprentices), demographics and tenure time were mostly in line with the expectations for hairdressers from the full spectrum of the working population [ 1 , 2 , 4 , 5 , 21 , 22 ]. While current smokers were found to a lesser extent than often described [ 3 , 21 , 22 , 32 ], the prevalence was comparable to current data from the German female population (18.6%) [ 33 ].…”
Section: Discussionsupporting
confidence: 58%
“…The exposed group had more complaints of symptoms related to the respiratory system than the unexposed group though the potential confounders were adjusted. [ 12 ] In a five-year follow-up study, it was seen that the duration of work is directly proportional to the decline in respiratory function. It was also seen that a few hairdressers even left their jobs because of developing respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited understanding of sex-specific differences in lung cancer risk (10). Some studies have explored occupations where females may be at a risk, such as hairdressing (11,12), and nail salons (13, 14), which may involve exposure to chemicals in hair dyes (11), and volatile organic compounds (14), respectively. Another study identified increased risk of lung cancer among female nurses with long duration of rotating night shift work, although this was only observed among smokers (15).…”
Section: Introductionmentioning
confidence: 99%